NILAI-NILAI SOSIAL PROFETIK DALAM RITUALITAS IBADAH PUASA RAMADHAN - Athoillah Islamy (Wawasan: Jurnal Kediklatan Balai Diklat Keagamaan Jakarta, 2021)
Ramadan fasting rituals have a big mission in shaping the social personality of a Muslim. This is because the obligation of fasting is a theocentric-oriented category of worship and an anthropocentric orientation. This study seeks to explore the predictive social values ​​contained in the mandatory religious fasting of Ramadan. This is library research with a philosophical normative approach. Meanwhile, the analytical theory used, namely the theory of social science (ISP), which Kuntowijoyo put forward, was in the form of values ​​of humanization, liberation, and transcendence. The study concludes that three prophetic social values can be taken from the spirituality of Ramadan fasting, including (1) faith commitment as a manifestation of transcendent values ​​, (2) fostering social piety character as a manifestation of liberation, (3) Social care as a manifestation of humanization.